2019
DOI: 10.33714/masteb.581725
|View full text |Cite
|
Sign up to set email alerts
|

First Observation of Loggerhead Sea Turtle Caretta caretta (Linnaeus 1758) Around the Shipwreck Used as an Artificial Reef in the Coasts of Gokceada Island, North Aegean Sea

Abstract: In this study, loggerhead sea turtle Caretta caretta (Linnaeus 1758) was observed for the first time around the shipwreck of coast guard boat in Ördek Yalağı located at Gökceada Island, North Aegean Sea. The shipwreck is at a depth of 24.8 m. The loggerhead sea turtle Caretta caretta was recorded exactly on the ground and 2 m away from the ship on the shore side of the ship. In this study, Caretta caretta was recorded for the first time in this water depth and around a shipwreck that was used as an artificial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Although there have been many studies conducted along Gökçeada coasts, such as the fish fauna from shallow waters, species composition, fish egg and larvae (Altın and Ayyıldız, 2018;Kocabaş and Acarli 2019;Acarli et al, 2020b;Daban et al, 2020); only one study on the status of P. nobilis population in Gökçeada has been found (Çanak et al, 2006). In this context, the current study aimed to determine the present status of the P. nobilis population in Gökçeada, which is located in the northernmost part of the Aegean Sea.…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been many studies conducted along Gökçeada coasts, such as the fish fauna from shallow waters, species composition, fish egg and larvae (Altın and Ayyıldız, 2018;Kocabaş and Acarli 2019;Acarli et al, 2020b;Daban et al, 2020); only one study on the status of P. nobilis population in Gökçeada has been found (Çanak et al, 2006). In this context, the current study aimed to determine the present status of the P. nobilis population in Gökçeada, which is located in the northernmost part of the Aegean Sea.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Yalçın Özdilek et al (2018a) reported 37 stranded sea turtles on the Northern Aegean and Sea of Marmara coasts, and 76.5 % of them were reported from the coast of Çanakkale. Kocabaş & Acarlı (2019) indicated seeing an alive adult male loggerhead sea turtle while scuba diving at Gökceada island, North Aegean Sea. In addition to these studies, Yalçın Özdilek et al (2018b) revealed that Gökçeada coasts at the Northern Aegean Sea are foraging habitats of the loggerhead sea turtles from isotopic signatures and they play a carnivorous role in the pelagic food web from the depletion in the mean δ13C value.…”
Section: Introductionmentioning
confidence: 99%